Educação infantil e relações de gênero: um estudo sobre significações de meninas e meninos na pré-escola - Pomini, Maria Laura Ferreira da Silva (2024)
This field research focuses on the interest in early childhood education and examines gender relations. The theoretical and methodological references are from SocioHistorical Psychology. The overall objective of this work was to analyze the significations constituted by children in early childhood education regarding gender relations. In this context, we analyzed the statements of 5 to 6-year-old children attending the preschool of a public early childhood education unit in the city of Estância Turística de Barretos, in the interior of the State of São Paulo. We aimed to explore the significations constituted about the social constructions of femininity and masculinity and the relationships that stem from them. Inspired by the methodological contributions of González Rey (2010), conversations were conducted in group meetings of girls and boys. For the analysis of the produced information, we resorted to the procedure of significant themes, inspired by the procedure of significations nucleus by Aguiar and Ozella (2013). The analysis provided an understanding that gender relations are a socially important theme, laden with aspects that are organized, within the children's significations, in an ambivalent manner, expressing themselves in both similarities and differences between genders. In the socialization among peers and educators, children develop and constitute their subjectivity amid various practices and activities that express social advances and setbacks in gender relations. The school, a socially significant institution for the development of children, also experiences ambivalence, either supporting/confronting gender issues or remaining silent. Public policies in this field become fragile in the school setting. Religious fundamentalism and the antigender debate are social movements that act as barriers to the promotion of gender education policies. However, from the children's statements, it was possible to identify the signification of resistance, revealing changes and advances concerning gender relations